Sex differences in the prevalence of vascular disease and risk factors in young hospitalized patients with psoriasis - Michael S. Garshick, MD, MS; Georgeta Vaidean, MD, PhD; Cyrus A. Nikain, BS; Yu Chen, PhD; Nathaniel R. Smilowitz, MD; Jeffrey S. Berger, MD, MS (Wolters Kluwer, 2019)
Background: Psoriasis is an inflammatory skin disease associated with atherosclerotic cardiovascular disease (ASCVD) risk factors and vascular disease. The relative impact of psoriasis on vascular disease is the strongest in young patients with psoriasis, yet data are lacking on how sex differences influence cardiovascular risk factors and vascular disease in these patients. Objective: This observational study aimed to identify the burden of cardiovascular risk factors and vascular disease in patients with psoriasis and to explore whether this burden is different between men and women age <35 years. Methods: Young (age ≥20 and <35 years) hospitalized patients with psoriasis from the United States National Inpatient Sample were compared with those matched patients without psoriasis. Vascular disease was defined as ASCVD and/or venous thromboembolic disease. Multivariable logistic regression was used to determine the associations between psoriasis, sex, ASCVD risk factors, and vascular disease. Results: Overall, patients with psoriasis (n = 18,353) were more often obese (16% vs. 6%); smokers (31% vs. 17%); and diagnosed with diabetes mellitus (10% vs. 6%), hypertension (16% vs. 8%), hyperlipidemia (6% vs. 2%), ASCVD (2.2% vs. 1.6%), and deep vein thrombosis (6% vs. 4%; all p < .001) compared with patients without psoriasis (n = 55,059; matched by age, sex, and race). When stratified by sex, women with psoriasis were more likely to have multiple cardiovascular risk factors and ASCVD (odds ratio: 2.6; 95% confidence interval [2.1-3.1]) compared with men with psoriasis (odds ratio: 1.2; 95% confidence interval [0.9-1.4]; interaction p < .01). The association between psoriasis and ASCVD in women remained unchanged after multivariable adjustment for traditional cardiovascular risk factors. Conclusion: Psoriasis was associated with cardiovascular disease and risk factors in young hospitalized patients, with stronger associations among women than among men. Keywords: Psoriasis, sex differences, vascular disease